Impact of the Addition of a Centrifugal Pump in a Preterm Miniature Pig Model of the Artificial Placenta - Charest-Pekeski, Alex J.; Cho, Steven K. S.; Aujla, Tanroop; Sun, Liqun; Floh, Alejandro A.; McVey, Mark J.; Sheta, Ayman; Estrada, Marvin; Crawford-Lean, Lynn; Foreman, Celeste; Mroczek, Dariusz; Belik, Jaques; et al. (Frontiers in Physiology, 2022)
The recent demonstration of normal development of preterm sheep in an artificial extrauterine environment has renewed interest in artificial placenta (AP) systems as a potential treatment strategy for extremely preterm human infants. However, the feasibility of translating this technology to the human preterm infant remains unknown. Here we report the support of 13 preterm fetal pigs delivered at 102 ± 4 days (d) gestation, weighing 616 ± 139 g with a circuit consisting of an oxygenator and a centrifugal pump, comparing these results with our previously reported pumpless circuit (n = 12; 98 ± 4 days; 743 ± 350 g). The umbilical vessels were cannulated, and fetuses were supported for 46.4 ± 46.8 h using the pumped AP versus 11 ± 13 h on the pumpless AP circuit. Upon initiation of AP support on the pumped system, we observed supraphysiologic circuit flows, tachycardia, and hypertension, while animals maintained on a pumpless AP circuit exhibited subphysiologic flows. On the pumped AP circuit, there was a progressive decline in umbilical vein (UV) flow and oxygen delivery. We conclude that the addition of a centrifugal pump to the AP circuit improves survival of preterm pigs by augmenting UV flow through the reduction of right ventricular afterload. However, we continued to observe the development of heart failure within a matter of days.